Wearing Out: Digital Precarity In Just-In-Time Retail - Van Oort, Madison (My University, 2018)
Wearing Out: Digital Precarity in Just-in-Time Retail investigates the booming but vastly understudied world of fast fashion. Glance at any list of the world’s wealthiest people, and alongside Bill Gates, you’ll find Amancio Ortega and Stefan Persson, who head multinational retail giants Zara and H&M, both of which are now found in almost every major city in the United States. This sector of retail—known for quickly designing, producing, circulating, and selling tremendous amounts of trendy, cheap clothing—is an increasingly important player in the global market. For my dissertation, I embarked on one of the first ethnographies of the industry: working undercover in two of the world’s largest fast fashion stores in New York City, interviewing dozens of front-line workers and labor activists, and attending corporate conferences. The manuscript advances both sociology of work and critical data studies by providing an on-the-ground account of how big data and surveillance shape the lives of low-status workers in an industry in flux. I argue that fast fashion represents a distinct regime of retail capitalism, in which fast fashion retail companies take advantage of big data and biometric technology to perfect just-in-time production practices in the retail workplace, reaping profits by creating commodities and workers designed to wear out and frequently turn over. This digital precarity, I find, is entangled with broader forms of precariatization, digitization, and policing throughout society, compounding insecurity for already marginalized populations. Finally, my ethnography reveals how collective struggles for racial, gender, and economic justice in and around retail spaces help advance a critical data praxis.
University of Minnesota Ph.D. dissertation. May 2018. Major: Sociology. Advisors: Teresa Gowan, David Pellow. 1 computer file (PDF); ix, 164 pages.
Keywords: fast fashion; labor; race; retail; surveillance; work